When black meets green: A review of the four pillars of India's energy policy. (July 2019) - Sokołowski, Maciej M.
Abstract: India is one of the most important global players in the energy sector in terms of production and consumption. The way in which the country shapes its energy policy not only affects India itself, but also the global climate action. On the one hand, India led by PM Narendra Modi declares the commitment to pro-climate actions, including the enhancement of the energy efficiency and renewable capacity. On the other hand, the development of India's conventional energy sector (coal) was indicated as one of the reasons for the US′ exit from the Paris Agreement. This dilemma lead to a discussion on the shape of India's energy policy, seen from the climate's standpoint. In this context, the article discusses the pillars of India's energy policy presented by Modi in 2016. The main energy pillars (access, efficiency, sustainability and security) are juxtaposed with the previous Indian strategic documents concerning the energy sector, including electricity (National Electricity Policy of 2005, Draft National Energy Policy of 2017). A climate-energy policy analysis is extended by legal comments on Indian energy law. As a result, the article draws a picture of India's energy policy and climate agenda in 'black' (conventional energy) and 'green' (renewable capacity) colours. Highlights: On the one hand, India declares its pro-climate attitude. On the other hand, PM Modi does not hide support for hydrocarbons, including coal. Enhancing sustainability in India collides with ensuring energy access and energy security. Usage of natural gas can be a 'middle approach' in Indian energy transition.